High Performance Multi‐Level Non‐Volatile Polymer Memory with Solution‐Blended Ferroelectric Polymer/High‐k Insulators for Low Voltage Operation. (10th June 2013) - Hwang, Sun Kak; Bae, Insung; Cho, Suk Man; Kim, Richard Hahnkee; Jung, Hee Joon; Park, Cheolmin
Abstract Polymer ferroelectric‐gate field effect transistors (Fe‐FETs) employing ferroelectric polymer thin films as gate insulators are highly attractive as a next‐generation non‐volatile memory. Furthermore, polymer Fe‐FETs have been recently of interest owing to their capability of storing data in more than 2 states in a single device, that is, they have multi‐level cell (MLC) operation potential for high density data storage. However, among a variety of technological issues of MLC polymer Fe‐FETs, the requirement of high voltage for cell operation is one of the most urgent problems. Here, a low voltage operating MLC polymer Fe‐FET memory with a high dielectric constant (k) ferroelectric polymer insulator is presented. Effective enhancement of capacitance of the ferroelectric gate insulator layer is achieved by a simple binary solution‐blend of a ferroelectric poly(vinylidene fluoride‐co‐trifluoroethylene) (PVDF‐TrFE) (k ≈ 8) with a relaxer high‐k poly(vinylidene‐fluoride–trifluoroethylene–chlorotrifluoroethylene) (PVDF‐TrFE‐CTFE) (k ≈ 18). At optimized conditions, a ferroelectric insulator with a PVDF‐TrFE/PVDF‐TrFE‐CTFE (10/5) blend composition enables the discrete six‐level multi‐state operation of a MLC Fe‐FET at a gate voltage sweep of ±18 V with excellent data retention and endurance of each state of more than 104 s and 120 cycles, respectively.